A qualitative systematic review of patients' experience of osteoporosis using meta-ethnography. Issue 1 (December 2016) - Barker, K.; Toye, F.; Lowe, C.
Abstract Summary We aimed to systematically review qualitative studies exploring the experience of living with osteoporosis to develop new conceptual understanding. We identified themes about the invisibility/visibility of osteoporosis, the experience of uncertainty of living with osteoporosis (OP) and living with an ageing body and the place of gender. Purpose The aim of this review was to systematically review the body of qualitative studies exploring the experience of living with either osteoporosis or osteopenia and to use meta-ethnography to develop new conceptual understanding. Methods We systematically reviewed and integrated the findings of qualitative research from four bibliographic databases (Medline, Embase, Cinahl, Psychinfo) to September 2015 in order to increase our conceptual understanding of the lived experience of osteoporosis and osteopenia. Articles were appraised for quality; each was independently read by two researchers to identify concepts which were compared and developed into a conceptual model. Results Our findings demonstrate that coming to terms with a diagnosis of osteoporosis is linked to its relative visibility or invisibility. For some, OP has not become manifest and self-identity is intact (biographical integrity). For others, OP is profoundly manifest and self-identity is no long intact (biographical fracture). We also demonstrate that overwhelming uncertainty pervades the experience of OP. Our final theme demonstrates how the experience of OP is set within a cultural context with certain views about ageing and gender. Conclusions Our synthesis has highlighted the wealth of qualitative data about osteoporosis and osteopenia. Despite the increasing body of literature on the subject, there remains a need to adjust our interactions with patients. This will allow clinicians to understand how patients can be helped to receive and understand their diagnosis and move forward in partnership with healthcare providers to promote optimal management of the disease.